Strategi Pengelolaan Limbah Pustaka Dalam Meningkatkan Pemberdayaan Masyarakat di Desa Muntang Kecamatan Kemangkon Kabupaten Purbalingga 2020 - Ningtyas, M.S.; Khasanah, Khasanah; Sari, siti Nurindah (Indonesian Journal of Geography Education, 2021)
Library is an infrastructure facility that contains a collection of good books in the form of print media, to manage in a special way in order to have intellectual needs in users through various ways of interaction of knowledge. With time the use of libraries began to decrease, because of the lack of interest in reading at the library and the lack of caring for rubbish and the library owner had the idea to get around using a 3-wheeled motorized wheelbarrow at the same time as having the idea to attract trash. Because the activity is very unique, creative and has a lot of visitors, therefore the activity synergizes between garbage and library and its concern for the environment and literacy. This study discusses "Literary Waste Management Strategies in Community Empowerment. The purpose of this research is to find out how the Literature Waste Management Strategy in community empowerment in Muntang Village, Kemangkon District, Purbalingga District, to find out the efforts made to improve literacy and care for the environment. This type of research used in this study is a qualitative descriptive approach. The informants used in this study were the Founder of the Library, Waste Management Library, Waste Bank Customers, Literature Waste Volunteers, Librarians among students, and parents. Data collection techniques in this study used observation and interviews to obtain primary data, and documentation to obtain secondary data. Based on research that has been done, Literature Waste Management in community empowerment in Muntang Village, Kemangkon District, Purbalingga Regency has two roles, namely the role in the field of Literacy (Education) and the environment. Fields in the field of Literacy (Education) are realized with the existence of GERNAS BAKU activities, writing training, and the socialization of the use of healthy internet for children and adolescents. In the field of environment, they are training in making ecobricks, making flowers from plastic bags, and making curtains made from used glass. In carrying out the way the Waste Management Library places itself as a facilitator